School Library Development Plan Application Based on Web - Abri Hadi; Mukramin Mukramin; Ramdana Ramdana (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2022)
Libraries are part of learning resources that must be owned by every school and college. Library make studentsseek knowledgeeasily. Vocational High School State (SMK) 2 Luwu is one of the secondary schools that has not implemented a website-based system. This is because the library of SMK Negeri 2 Luwu still uses a manual system. As in lending and returning services, they still use a recording system in the borrowing book. In addition, when there are new books added, the librarian does not record the book data, only gives the ID to the book and immediately stores it on the appropriate shelf in the book category. The method used in this research is the waterfall method. This application is designed using the UML model, and built using the PHP programming language and MySQL database